HEMATOLOGI IKAN NILA (Oreochromis niloticus) DARI WADUK OLIGOTROFIK DAN EUTROFIK - Diana Arfiati; Rizky Kusma Pratiwi; Zakiyyah Nur Inayah (Pattimura Proceeding, 2022)
Hematological observations of Nile tilapia (Oreochromis niloticus) were carried out in oligotrophic waters (Wonorejo Reservoir) in July-August 2018 and eutrophic waters (Selorejo Reservoir) in March-April 2021. Both reservoirs are located in East Java, Indonesia. The number of fish samples from the Wonorejo Reservoir was 80 fish, while the sample from the Selorejo Reservoir was 108 fish. Sampling was carried out 3 times every 2 weeks. The erythrocyte, hemoglobin, and hematocrit levels of tilapia from Selorejo Reservoir (eutrophic waters) were lower than those from oligotrophic waters. The condition of low levels of erythrocytes, hemoglobin, and hematocrit indicates that fish are under stress. The leukocytes and micronuclei were higher in fish from eutrophic waters which were thought to be less healthy. The hematology of Nile tilapia from the Wonorejo Reservoir (oligotrophic) was in good condition, while the Nile tilapia from the Selorejo Reservoir (eutrophic) was not in good condition, which was thought to be due to the eutrophic condition of the waters there was an imbalance of physico-chemical water, so that the health of the fish was disturbed